Efficient Removal of Cationic and Anionic Dyes from Aqueous Solutions using Regenerated Silk Fibroin Beads - Nitayaphat, Walaikorn; Jintakosol, Thanut (Asian Journal of Chemistry, 2020)
Regenerated silk fibroin beads (rSFB) were successfully prepared and applied to adsorbing methylene blue and Lanasyn Navy M-DNL. The effects of contact time, initial pH and initial concentration of dyes were analyzed. The experimental results showed that, the adsorption was pH dependent with a high removal efficiency of methylene blue in basic range and high removal of Lanasyn Navy M-DNL in acidic range. The adsorption process was analyzed by using Langmuir and Freundlich isotherm models and the Langmuir isotherm model showed the best fitting to the isotherm data. The maximum adsorption capacities for methylene blue and Lanasyn Navy M-DNL were 47.55 and 78.74 μmg/g, respectively. The kinetics study showed that the adsorption process followed the second order kinetic model. The SEM images demonstrated that after adsorption the dye was adsorbed onto the regenerated silk fibroin beads surface. The adsorbent was stable and active for up to five successive cycles. Regenerated silk fibroin beads showed to be an advantageous adsorbents in terms of availability, which is beneficial for the wastewater treatment.